Research on the Innovation and Transformation of Aesthetic Style of Yangjiabu New Year Posters - Huiru, Cao; Hassan, Dr. Rahah Bt. (Studies in Social Science & Humanities, 2025)
This study takes the traditional folk art of China — Yangjiabu New Year posters as its research subject, systematically examining the evolution of formalist aesthetic styles in five historical periods: the Ming Dynasty, Qing Dynasty, Republican Era, New China, and contemporary times. The research employs case analysis, documentary research methods, and field investigations, delving into the five formal elements mentioned in Roger Fry’s formalism theory—line, color, space, volume, and light—to reveal how Yangjiabu New Year posters have developed unique artistic expressions and aesthetic characteristics under different cultural environments and social demands. The findings indicate that the aesthetic style of traditional Yangjiabu New Year posters can no longer meet contemporary societal aesthetic needs, making innovation and transformation imperative. The conclusion emphasizes that formalism theory not only helps reveal the formal beauty and emotional depth of Yangjiabu New Year posters but also provides theoretical support for their contemporary expression in the digital age. Limitations of this study include insufficient sample concentration, inadequate exploration of digital applications, and the need for enhanced interdisciplinary integration. Future research should delve deeper into the pathways of interactive art manifestations in digital media for New Year posters and strengthen comparative studies with other folk art categories to expand understanding of the contemporary transformation of intangible cultural heritage. This paper offers new perspectives and methodological support for art history, design studies, and intangible cultural heritage protection research.